Remedial powers and the fight against impunity: review on the reception of the barrios altos standard in Brazil, Chile, Peru and Uruguay - Gurmendi Dunkelberg, Alonso (2018)
In this article, the authors analyze the reception of the judicial doctrine of the void ab initio of internal amnesty laws contrary to the Inter-American Convention on Human Rights, set by the Inter-American Court since the Barrios Altos case.In these order of ideas, the various social and political processes developed inside the countries attached to this international court are taken into account, who would be the receivers of the court’s decisions’ content. However, as pointed out by the authors, each nation’s context has ended up in a particular assimilation and even a sharp opposition from the national authorities to this judicial doctrine.